RELATION OF WORKER CHARACTERISTICS AND PERSONAL DUST LEVEL TO THE VITAL LUNG CAPACITY OF WORKERS IN THE FURNITURE INDUSTRY - Putri Arini (The Indonesian Journal of Public Health, 2020)
ABSTRACTFurniture industry is one of growing industry in Indonesia which has rapid growth. The process of its production brings one complex problem; wood dust. Workers who engage in the production process will have problem with their lung which can lead problem into their respiratory system. It is caused by the wood dust that mixed into oxygen they breath. Furthermore, if this condition happens in long period, it become a serious problem; impairment of vital pulmonary capacity. Besides, the impairment of vital pulmonary capacity can occur due to workers characteristics or conditions such as age, working history, working period, shelf period, illness history, smoking habit, diet, exercise, and the wearing of APD. The purpose of this research was to find out the relation between workers characteristics and personal dust level within vital capacity of lung. This research used cross sectional design with 17 respondents which was took by simple random sampling technique. This research took place at furniture industry X in Tubanan, Tandes, Surabaya, started from April to May 2018. Data was analysed using chi-square test and independent t-test with accuracy up to 95%. Data was collected through interview, observation, and measurement. The result of this research showed that there was correlation between working period, shelf period, and smoking habit within vital pulmonary capacity. The conclusion of this research was that working period, shelf period, smoking habit had important role to workers vital pulmonary capacity in furniture industry.Keywords: worker characteristics, wood dust, vital capacity of lung, furniture industry